Pengukuran Overall Equipment Effectiveness (OEE) di PT Astra Otoparts Tbk. Divisi Adiwira Plastik - Wijaya, Christian Yoko; Widyadana, I Gede Agus (Jurnal Titra, 2015)
Overall equipment effectiveness (OEE) is a performance measurement tool that can measure the production losses and identify improvement potential. PT Astra Otoparts Tbk. Adiwira Plastics Division (PT AO AWP) is a manufacturing company of automotive components made from plastic which always perform continuous improvement to increase productivity. The problem is the lack of OEE calculation standar prosedure for family mold usage in plastic injection machines. The other problem is the production data on the web which used to measure the performance of the production process can not show the actual condition of plastic injection machine. The cause of this problem are database system, shot per hour (SPH) system updates, and admin errors in data input. Error in production data can lead to errors in performance calculation result of production process as well as errors in set improvement point analysis. The OEE calculation result using production data from Laporan Hasil Produksi is 86%. the result of this calculation is analyzed to obtain the most influential factor and get the root causes for the decisions of improvement.